2022
DOI: 10.1002/jcop.22793
|View full text |Cite
|
Sign up to set email alerts
|

Generating youth dialogue through the literary arts: A citywide youth health collaboration in the U.S.

Abstract: A process and outcomes evaluation was conducted of a citywide literary-arts initiative designed to reduce stigma, amplify underrepresented narratives, and generate dialogue about violence. Over 4 months, students in 85 middle schools read a novel addressing mental health and violencerelated themes. As a collaboration between a public school district and public library system, the program's classroom activities emphasized dialogue, while coordinated library events supported community engagement. Students comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It was also revealed that students appreciated the book, found it influential, discussed it with friends, and wanted even more opportunities to engage with the content. Findings and recommendations that will bolster OBB and support similar community-wide reading programs are detailed in a peer-reviewed journal article in Journal of Community Psychology ( Golden et al, 2022 ) and in a comprehensive report delivered to stakeholders in BCPS, EFPL, and the T. Rowe Price Foundation.…”
Section: Itf Case Studiesmentioning
confidence: 99%
“…It was also revealed that students appreciated the book, found it influential, discussed it with friends, and wanted even more opportunities to engage with the content. Findings and recommendations that will bolster OBB and support similar community-wide reading programs are detailed in a peer-reviewed journal article in Journal of Community Psychology ( Golden et al, 2022 ) and in a comprehensive report delivered to stakeholders in BCPS, EFPL, and the T. Rowe Price Foundation.…”
Section: Itf Case Studiesmentioning
confidence: 99%